Anthelmintic Activity of Goat's Milk: Transmission Electron Micrographic Evidence - Omaima Adil Najm; Mohamed Adel Elkadi; Wan Omar Abdullah; Noor Amiza Zainal Abidin; Faizul Helmi Addnan; Nur Fariha Mohd Manzor; Fadlul Azim Fauzi Mansur (Scholars Middle East Publisher, 2024)
Non-Indexed Publication